The mechanical efficiency of the o soto gari technique when applied to judokas of different heights - Melo, S.; Santos, S.; Teixeira, J.; Piucco, T. (Archives of Budo, 2012)
Background and Study Aim: The biomechanical efficiency of judo throw techniques depends on the anthropometric characteristics of the opponent. This study aimed to evaluate the mechanical efficiency of the o soto gari technique when applied to judoists of different heights in relation to the thrower. Materials and Methods: The following factors were compared: the tori angular variation of knee, hip and trunk; the total and partial performance time and the displacement of the vertical trajectory of the tori center of mass (Delta CM). Three uke of shorter, similar and taller stature than the tori were kinematically analyzed performing ten o soto gari throws. The images were recorded at 180 Hz using the Peak Motus System 3D. The data were analyzed by descriptive statistics, ANOVA and post-hoc Tukey (p= 0.05). Results: The mechanical efficiency of angular displacement was greater when the tori was throwing shorter uke; the throwing time was shorter against shorter uke; the tori ?CM was greater when throwing shorter uke. Conclusion: We conclude that the o soto gari technique is more efficient when applied to shorter opponents.